Experimental investigation on silica dust lofting due to charging within micro-cavities and surface electric field in the vacuum chamber. Issue 10 (15th May 2019) - Orger, Necmi Cihan; Toyoda, Kazuhiro; Masui, Hirokazu; Cho, Mengu
Abstract: The charged dust particles can be mobilized electrostatically by the repulsion between the adjacent grains and the surface electric field due to the incoming electron current and the charge accumulation within the micro-cavities. In this study, the experimental results of the initial vertical launching velocities and the maximum dust heights are compared with the estimated values for the lofted spherical dust grains by the patch surface charging equations. Silica particles with the sizes between <6 and 45 µm in radius are loaded on a graphite plate, and they are exposed to the electron beam with 450 eV energy under 4 × 10 −3 Pa vacuum chamber pressure. During the first set of the experiments, the dust samples are tested without an initial compression process and an additional horizontal electric field. Second, the dust samples are compressed by two different weights in order to increase the packing density under approximately 780.7 Pa and 3780 Pa. Finally, the dust grains are placed between the two parallel aluminum plates to apply approximately 2000 V/m and 4800 V/m horizontal electric field. A high-speed camera is used to record the transportation of the dust grains together with a microscopic telescope, and the results point out that the patch surface dust-charging model estimations are in agreement with the first experiments. On the other hand, the dust particles from the compressed samples are lofted with higher velocities than the estimations, and the number of the dust lofting observations decreases significantly, which demonstrates the importance of the micro-cavities and the increased charging requirement to overcome the contact forces. When the horizontal electric field is present, the initial vertical launching velocities are measured to be lower than the other experiments, which can be attributed to the decreased charging requirement for the dust lofting as a result of inter-particle collisions and rolling motion. According to the experimental results, the electrostatic dust transportation can be controlled not only by the ambient plasma and the solar irradiation on the airless planetary bodies, but also by the surface properties such as the contact surfaces between the dust grains, the number of the micro-cavities related to the packing density, and the presence of the horizontal electric field contributing to the external forces by other particle motions.